DOES UNEMPLOYMENT LEAD TO CRIMINAL ACTIVITIES? EMPIRICAL ANALYSIS OF CEE ECONOMIES - Lojanica, Nemanja; Obradović, Saša (The European Journal of Applied Economics, 2020)
This paper attempts to shed light on the linkages between criminal behavior and unemployment, with special reference to Central and East European countries (CEE). The adequacy of this paper relies on the premise that econometric modeling of the relation between these variables is very important for explanation of economic and social growth. Our result is in line with the premise that crime goes up when unemployment rises. These findings suggest that to combat crime, all strategies oriented to mitigate unemployment should be investigated. Also, in order to successfully mitigate crime, governmental authorities in the CEE economies need to achieve macroeconomic stability.